Gerakan Buruh Pasca Soeharto: Politik Jalanan di Tengah Himpitan Pasar Kerja Fleksibel - Muhtar Habibi (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2013)
Labor movement after Soeharto shows different trend compare to the many view of the observers before. In the midst of the crush of neoliberal labor market flexibility, workers still often performs various street protests. The rising of minimum wage and changes in employment status towards more profitable one, are some workers material benefits gained through their street protest. Moreover, street protest also contributes to the making of collective workers identity. The high intensity of the street actions spawned the backlash from the capital and state. However, this attack rather than weaken the labor movement, instead it has the potential to encourage greater unity needs of the workers. The backlash from the capital and state during growing economic circumstances provide momentum to the emerging needs of modern interest organizations: a labor’ party. The future of the establishment labor’ party will depend on how much effort of the progressive elements in trade union able to leverage on the one hand a growing economy condition, and at the same time politically able to use reprisals of state and capital against their movement to create the need for the formation of an independent labor party for the rank and file workers.